Studi Pemanfaatan Pati Sagu (Metroxylon Sp) dan Daging Ikan Belut (Monopterus Albus) Dalam Pembuatan Sosis - Fadmi, Andriyani; Herawati, Netti; Restuhadi, Fajar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research to get formulation the best of sausage from benefit of sago essence and meat of eel. This research was carried out experiments using a Completely Randomized Design (CRD) with 4 treatments and 4 replications in order to obtain 16 experimental units. The data obtained were statistically analyzed using Analysis of Variance (ANOVA). If the calculated F is greater than or equal to F table then continued with DNMRT test at 5% level. Sensory evaluation data show that by using PCA and cluster analysis, evaluation organoleptic by analysis hedonic with spider web to see attribute that protrude from every treatment. According to proceeds of chemists analysis and organoleptic experiment the best sausage get from 5% tapioca essence and 10% sago essence so that treatment of TSB3 by characteristic like: activity of water 71,25%, activity of ashes 1,8%, activity of protein 8,9 %, activity of fat, activity 4,80%, carbohydrate 13,12% and experiment of color hedonic 2,24 %. Organoleptic evaluation by hedonic toward color 2,24 (rather agree), taste 1,97 (rather agree), 2,74 (rather agree) form 2,28 (rather agree) and over all evaluation 2,22 (rather agree) then organolepic evaluation by descriptive to color 2,52 (white grey), taste 2,20 (rather taste of eel), 2,43(rather stink), form 2,35 (elastic). Kata kunci: susu fermentasi, Lactobacillus plantarum 1 R.11.1.2, kacang hijau dan kacang kedelai. Keywords: Sosis, Pati Sagu, Belut.